2011
DOI: 10.1159/000328769
|View full text |Cite
|
Sign up to set email alerts
|

DP2 (CRTh2) Antagonism Reduces Ocular Inflammation Induced by Allergen Challenge and Respiratory Syncytial Virus

Abstract: Background: Allergic conjunctivitis is characterized by itchy, watery and swollen eyes which occur in response to exposure to seasonal or environmental allergens. The early phase reaction of allergic conjunctivitis is primarily mediated by mast cell degranulation while the late phase reaction is driven by Th2 cells and eosinophils. Prostaglandin D2 (PGD2), released from mast cells, is present in allergic conjunctival tears and may elicit classical allergic responses via interaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Here, our findings suggest that IL-33 might also dampen antiviral immunity via the induction of h-PGDS expression and downstream PGD2 production. Others have shown that DP2 blockade decreases RSV-induced ocular inflammation using a mouse model of allergic conjunctivitis (41). However, the investigators did not assess viral load or elucidate the mechanism by which DP2 antagonism was protective.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our findings suggest that IL-33 might also dampen antiviral immunity via the induction of h-PGDS expression and downstream PGD2 production. Others have shown that DP2 blockade decreases RSV-induced ocular inflammation using a mouse model of allergic conjunctivitis (41). However, the investigators did not assess viral load or elucidate the mechanism by which DP2 antagonism was protective.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine and sheep isolates of RSV have caused conjunctivitis with mild respiratory disease in lambs and cattle (132)(133)(134)(135), highlighting the ability of this virus to cause ocular complications in nonhuman species. Several potential approaches to mitigate ocular inflammation following RSV infection are under investigation, including anticytokine treatments and the use of protein inhibitors (27,136,137). Considering the high burden of disease associated with this virus in humans, even a low level of documented ocular disease following RSV infection indicates a public health need to better understand this property.…”
Section: Respiratory Syncytial Virus Respiratory Syncytial Virus (Rsmentioning
confidence: 99%
“…It correlates with the severity of the disease on the one hand, and levels of PGD 2 on the other hand (78). Exogenously applied PGD 2 and DP2 agonists provoke peripheral blood eosinophilia and infiltration of eosinophils into the conjunctiva, lung, nose, and skin in animal models (30, 38, 7982), whereas pharmacological blockade of DP2 can ameliorate models of atopic dermatitis, asthma, rhinitis, and conjunctivitis (8388). Interestingly, DP2-deficient mice develop a normal chronic allergic inflammatory response to allergen challenge after sensitization and challenge, while the acute inflammatory response and eosinophil infiltration in the skin are abrogated (89).…”
Section: Targeting Pgd2 Signaling In Eosinophilic Diseasesmentioning
confidence: 99%